Novel near-infrared pH-sensitive cyanine-based fluorescent probes for intracellular pH monitoring. (November 2019) - Jin, Di; Wang, Bowei; Hou, Yuqing; Du, Yuchao; Li, Xue; Chen, Ligong
Abstract: Real-time monitoring of intracellular pH fluctuation is of great significance for diagnosis of diseases and study of related physiological and pathological processes. A novel near-infrared (NIR) pH-activated parent probe4 was developed, and further functionalized to afford probes6 and7 . With the decrease of pH from 11 to 2, they all exhibited a new absorption peak and strong fluorescence emission in NIR region, accompanied by rapid solution color change from pink to pale green. Moreover, the probes' fluorescence responses toward pH fluctuations were reversible and stable, and the pseudo-linear relationship between the fluorescence intensity and pH value can be used to detect pH value in 2.76–6.45 range quantitatively. Finally, probe6 and7 were successfully applied to monitor the fluctuation of intracellular pH by a fluorescence turn-on mode, and the imaging results confirmed their low cytotoxicity and satisfactory cell-membrane permeability, as well as their application prospect in disease diagnosis (such as tumor specific imaging) or assist in study of pH-related biological processes in wide acidic environment. Graphical abstract: Image 1 Highlights: Novel pH-sensitive NIR cyanine-based fluorescent probes (4, 6, 7 ) were developed. All probes exhibited colorimetric and fluorescence responses to pH fluctuations. The three probes could achieve quantitative detection of pH value in 2.76–6.45. Probe7 is a ratio fluorescent probe for pH. Probe6 and7 were successfully applied to monitor intracellular pH fluctuations.